Implementation of Local Wisdom of Minang Culture (Studies Of The Minang Diaspora in Surabaya) - Trisa, Yosi; Suprijono, Agus; Jacky, M (The Indonesian Journal of Social Studies, 2019)
The aim of the study was to understand how the application of Minang Culture Local Wisdom values "in the earth is grounded, there is the sky dijunjuang" in the Context of Ethnopedagogy by Perantau Minang in the City of Surabaya. This research is qualitative in nature with an ethnographic approach that was carried out for three months (August-October 2018) to Minangkabau migrants in the city of Surabaya. The results of the study show that there are at least five Minangkabau cultural values that are very important to be included as part of the ethopathic material. The nine cultural values are: 1) Caring for and maintaining Mother Language; 2)â€œDima bumi dipijak, disitu langit dijunjuangâ€; 3)â€œNan elok dek awak katuju dek urang; Lamak dek awak lamak dek urang; Sakik dek awak sakik dek urangâ€; 4)â€œKaratau madang di hulu, Babuah babungo balun; Marantau Bujang dahulu, Di rumah baguno balunâ€; 5)â€œBaraja ka na manang, mancontoh ka nan sudahâ€; dan â€œTakuruang nak dilua, taimpik nak diatehâ€; 6) â€œYang buta penghembus lesung, yang pekak pelepas bedil, yang lumpuh penghuni rumah, yang kuat pemikul beban, yang bodoh untuk disuruh-suruh, dan yang pintar lawan berunding.â€; 7) â€œHiduik baraka, baukue jo bajangkoâ€; 8) â€œNan tuo dihormati, nan ketek disayangi, samo gadang bawo bakawan, ibu jo bapak diutamokan.â€;9) â€œAdat basandi syarak, syarak basandi kitabullahâ€Â Keywords: ethnopedagogy, local wisdom, Minangkabau culture.